2005
DOI: 10.1074/jbc.m501784200
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-induced Chromatin Remodeling at the c-myc Gene Involves the Local Exchange of Histone H2A.Z

Abstract: The post-translational modification of histones and the incorporation of core histone variants play key roles in governing gene expression. Many eukaryotic genes regulate their expression by limiting the escape of RNA polymerase from promoter-proximal pause sites. Here we report that elongating RNA polymerase II complexes encounter distinct chromatin landscapes that are marked by methylation of lysine residues Lys 4 , Lys 79 , and Lys 36 of histone H3. However, neither histone methylation nor acetylation direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
65
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 43 publications
9
65
0
1
Order By: Relevance
“…In agreement with that model, Farris et al have shown that transcriptional activation of the c-myc gene is accompanied by local displacement of H2A.Z within the transcribed region and incorporation of the canonical H2A. 32 We therefore propose that random incorporation, when coupled to targeted eviction, can lead to a specific distribution pattern, just as if the SWR complex includes a protein, Bdf1, which recruits SWR to promoters by virtue of the interaction of its bromo-domain with acetylated nucleosomes. [28][29][30] In mammalian cells, two proteins have been shown to target H2A.Z to promoters.…”
Section: Non-targeted Incorporation Of H2azmentioning
confidence: 55%
“…In agreement with that model, Farris et al have shown that transcriptional activation of the c-myc gene is accompanied by local displacement of H2A.Z within the transcribed region and incorporation of the canonical H2A. 32 We therefore propose that random incorporation, when coupled to targeted eviction, can lead to a specific distribution pattern, just as if the SWR complex includes a protein, Bdf1, which recruits SWR to promoters by virtue of the interaction of its bromo-domain with acetylated nucleosomes. [28][29][30] In mammalian cells, two proteins have been shown to target H2A.Z to promoters.…”
Section: Non-targeted Incorporation Of H2azmentioning
confidence: 55%
“…Several genome-wide studies of yeast H2A.Z occupancy have shown that this variant localizes to the promoters of thousands of euchromatic genes, and its presence is required for the optimal transcriptional activation of many of these genes (Guillemette et al, 2005;Li et al, 2005;Raisner et al, 2005;Zhang et al, 2005). In contrast with the situation in yeast, cytological and genetic studies suggest that in metazoans H2A.Z may also play a role in heterochromatin formation and/or maintenance (Rangasamy et al, 2003;Swaminathan et al, 2005), although this variant has been observed at the 59 ends of several active genes in human and chicken cell lines (Bruce et al, 2005;Farris et al, 2005). However, null mutations in mouse and Drosophila H2A.Z 1 To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 83%
“…Other genes involved in cell-cycle regulation (non-histone chromosome protein 2-like) and chromatin organization (histone H2A family member Z and histone H5) are also upregulated in GH transgenic liver (Table 4). Histone H2A family member Z has various functions in transcriptional regulation and maintenance of genomic stability (Farris et al 2005). Therefore, its induction in growth-enhanced salmon liver may be a part of a mechanism by which GH transgenic cells control genomic fidelity in a hyper-proliferative state.…”
Section: Cellular Proliferation and Stress Response In Gh Transgenic mentioning
confidence: 99%